Relative Deprivation and Game Addiction in Left-Behind Children: A Moderated Mediation - Yang, Banglin; Cai, Ge; Xiong, Cancan; Huang, Jin (Frontiers in Psychology, 2021)
Previous findings show that relative deprivation has a profound influence on game addiction, but the potential mediating and moderating mechanisms are unclear, especially for left-behind children. The present study therefore examined the relationship between relative deprivation and game addiction, the mediating effect of deviant peer affiliation, and the moderating effect of beliefs about adversity in a sample of left-behind children. A total of 952 left-behind children (mean age = 13.67 years, SD = 1.34) participated in this study. The participants anonymously completed a battery of questionnaires, including the Relative Deprivation Scale, the Deviant Peer Affiliation Scale, the Beliefs about Adversity Scale, the Game Addiction Scale, and demographic variables. After controlling for gender, left-behind category, and socioeconomic status, the moderated mediation model showed that (a) relative deprivation significantly and positively predicted game addiction in left-behind children; (b) The mediation analysis showed that the positive association between relative deprivation and game addiction in left-behind children was mediated by deviant peer affiliation; (c) Beliefs about adversity moderated the association between relative deprivation and deviant peer affiliation and were weaker for left-behind children with higher levels of beliefs about adversity, consistent with the risk-buffering model, but the relationship between relative deprivation and game addiction was stronger for left-behind children with higher levels of beliefs about adversity, consistent with the reverse risk-buffering model. These findings have crucial implications for the prevention and intervention of game addiction in left-behind children.